2013
DOI: 10.1007/s00284-013-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-Size, Small RNAs in Escherichia coli

Abstract: Noncoding small regulatory RNA molecules control gene expression and microRNAs provide one of the best examples in eukaryotes. However, bacterial RNAs of comparable size to eukaryotic microRNAs have received little attention. Here, we demonstrate the existence of microRNA-size, small RNAs (msRNAs) in the model bacterium Escherichia coli. We examined the small RNAs in E. coli using a deep sequencing approach, and analyzed 33.2 million small RNA clone reads after size fractionation. Bioinformatic analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…8,[42][43][44] Their existence in bacteria implies that these kinds of small RNAs are evolutionarily well-conserved from viruses and bacteria to mammals and that research into msRNA-mediated gene regulation may shed light on bacterial genetics.…”
Section: Srna In Bacteriamentioning
confidence: 99%
“…8,[42][43][44] Their existence in bacteria implies that these kinds of small RNAs are evolutionarily well-conserved from viruses and bacteria to mammals and that research into msRNA-mediated gene regulation may shed light on bacterial genetics.…”
Section: Srna In Bacteriamentioning
confidence: 99%
“…In fact, it has previously been suggested that bacteria, such as E. coli and Streptococcus mutans, produce OMVs that contain microRNA-like molecules [33,34]. However, the secondary structures of these 'microRNA-size' RNAs that the authors reported did not resemble those of eukaryotes' microRNAs.…”
Section: Glossarymentioning
confidence: 79%
“…Such molecules were found in Streptococcus mutans in 2011 [47] and in E. coli in 2013 [48], although their functions remain to be determined. Another microRNA of bacterial origin has been identified in Mycobacterium marinum , a fish pathogen able to produce a unique mycolactone toxin, mycolactone F [21].…”
Section: Something Smaller Than Srnas—true Micrornas In Prokaryotimentioning
confidence: 99%
“…All the above-presented prokaryotic microRNA-size molecules [20,21,22,47,48,49] have been identified by next generation sequencing (NGS). Such an experimental approach and bioinformatics analysis allowed for extracting large amounts of data and the identification of, e.g., more than 400 [48] or more than 900 [47] individual RNAs of microRNA size (15–26 nt) in a single experiment.…”
Section: Something Smaller Than Srnas—true Micrornas In Prokaryotimentioning
confidence: 99%
See 1 more Smart Citation